The Politics of Benchcraft: The Role of Judges in Mental Health Courts. Issue 2 (28th November 2016) - Castellano, Ursula
Abstract : Mental health courts (MHCs) offer community‐based treatment in lieu of criminal prosecution for chronic offenders with psychiatric disabilities, and MHC judges enjoy expanded powers to achieve the court's objectives. Because scholars know little about how judges transition into a new occupational role in the problem‐solving courtroom, this ethnographic study of four MHCs in the United States focuses on how judges learn to orchestrate their responses to treatment noncompliance in this novel court setting. The goal of this article is to examine the professionalization of MHC judges and the emergent craft of therapeutic adjudication. To achieve this goal, I investigate judicial strategies for motivating, questioning, and defending participants accused of wrongdoing. I conclude that the art and practice of problem‐solving justice requires judges to rise to the larger institutional challenges embedded in the alternative courtroom, a process I call the politics of benchcraft.